Notes on the montane Indo-Iranian species in Plantago subgenus Plantago (Plantaginaceae) - Hassemer, Gustavo (Phytotaxa, 2018)
A series of nomenclatural and taxonomic misunderstandings have surrounded the montane Indo-Iranian species in Plantago subgenus Plantago. This work has the objective of clarifying the nomenclature and taxonomy for the species and subspecies names available for these plants, in order to determine the correct species names for these entities. More specifically, P. tatarica is here lectotypified and re-established, P. griffithii is re-established, and P. aitchisonii is synonymised with P. griffithii. I provide here images of the types of the names studied, and also an identification key to Plantago subgenus Plantago in the Indo-Iranian region (Afghanistan, Bangladesh, India, Iran, Nepal, Pakistan and Sri Lanka).